Surface Expression of a Protective Recombinant Pertussis Toxin S1 Subunit Fragment in Streptococcus gordonii - Lee, Song F. (American Society for Microbiology, 1999)
In this study, the expression of the Bordetella pertussis S1 subunit was tested in Streptococcus gordonii, a commensal oral bacterium which has the potential to be a live oral vaccine vehicle. The DNA fragment encoding the N-terminal 179 amino acids of the S1 subunit was ligated into the middle part of spaP, the surface protein antigen P1 gene originating from Streptococcus mutans. The resulting construct, carried on the Escherichia coli-Streptococcus shuttle vector pDL276, was introduced into S. gordonii DL-1 by natural transformation. One of the transformants (RJMIII) produced a 187-kDa protein (the predicted size of the SpaP-S1 fusion protein) which was recognized by both the anti-pertussis toxin (anti-PT) and anti-SpaP antibodies, suggesting that an in-frame fusion had been made. Results from immunogold-electron microscopic studies and cellular fractionation studies showed that the fusion protein was surface localized and was mainly associated with the cell wall of RJMIII, indicating that SpaP was able to direct the fusion protein to the cell surface. A rabbit antiserum raised against heat-killed S. gordonii RJMIII recognized the native S1 subunit of PT in Western blotting and showed a weak neutralization titer to PT by the Chinese hamster ovary cell-clustering assay. BALB/c mice immunized with the heat-killed S. gordonii RJMIII were protected from the toxic effect of PT in the leukocytosis-promoting and histamine sensitization assays. In conclusion, a fragment of the S1 subunit of PT was successfully surface expressed in S. gordonii; the recombinant S1 fragment was found to be immunogenic and could induce protection against the toxic effect of PT in mice.